Allene Relay: Palladium‐Catalyzed Bicyclization of Allene‐Propargylic Carbonates with Geminal Bis(nucleophile)s1. Issue 41 (22nd August 2013) - Ye, Juntao; Ma, Shengming
<x xml:space="preserve">Abstract</x> Pass the baton: The title reaction affords synthetically attractive bicyclo[4.3.0] skeletons in up to 85 % yield by three consecutive CC bond formations in a single operation (see scheme; DMF=N, N‐dimethylformamide, DMSO=dimethyl sulfoxide, Ts=4‐toluenesulfonyl). The challenge of efficient axial‐to‐central chirality transfer involving π‐allyl palladium intermediates has been also realized. Mechanistic studies are discussed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>